Efeitos da oxima butano-2,3-dionatiossemicarbazona frente ao dano testicular causado por cádmio em camundongos - Freitas, Mayara Lutchemeyer de (2014)
We investigated the action of butane-2,3-dione thiosemicarbazone oxime against the testicular damage caused by cadmium chloride (CdCl2) in mice swiss adult male. The animals received a single injection of CdCl2 at the dose of 5 mg/kg, intraperitoneally, and after thirty minutes, the oxime was administered subcutaneously at the dose of 10 mg/kg. Twenty four hours after administration of the oxime, the animals were euthanized the blood were collected and after killed the testes were removed for analysis. The parameters determined were δ-aminolevulinate dehydratase (δ-ALA-D), myeloperoxidase (MPO), glutathione-S-transferase (GST) and glutathione peroxidase (GPx) activities, in testicular tissue. The levels of thiobarbituric acid-reactive substances (TBARS), nonprotein thiols (NPSH), ascorbic acid and the quantity of cadmium in testes were also evaluated. In addition, levels of testosterone in serum and cytokines (proinflammatory, IL-1, IL-6, TNF-α, IFN-γ and anti-inflammatory IL-10) were determined. Histological analysis of testicular tissue was also performed. Our results demonstrated that the oxime was effective in restoring partially the inhibition in δ-ALA-D activity induced by CdCl2. The activation of MPO and increase in IL-1, IL-6, TNF-α and IFN-γ levels induced by CdCl2 were also reduced by oxime. IL-10, which was reduced by cadmium, was partially restored by oxime administration. In addition, the oxime was effective in restoring the increase in TBARS levels and partially the reduction on NPSH levels induced by CdCl2. However, the oxime did not have action on the decreased levels of ascorbic acid induced by CdCl2 or on the decrease in enzymatic activity of GST and the increased enzymatic activity of GPx caused by CdCl2. Our results demonstrated that oxime was effective in restoring the histological alterations induced by CdCl2, preventing the loss of elongated spermatids. In addition, oxime was able to increase the testosterone levels reduced by cadmium exposure. In conclusion, the oxime tested was effective in reducing the testicular damage induced by CdCl2 in mice. The beneficial effects of this oxime are related to its antioxidant and anti-inflammatory action.